Kedudukan Majelis Kehormatan Disiplin Kedokteran Indonesia dalam Penyelesaian Sengketa Medis - Kastania Lintang; Hasnati Hasnati; Bahrun Azmi (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to analyze the position of the Indonesian Medical Disciplinary Board (MKDKI) in the settlement of medical disputes. This study uses a normative juridical research method with a statute approach and a conceptual approach. Medical disputes due to alleged violations of medical discipline should be resolved through the Indonesian Medical Disciplinary Board, however currently there are still medical disputes that are reported to the court without going through the Indonesian Medical Disciplinary Board. The results of this study show that, there is still legal uncertainty regarding the resolution of medical disputes between doctors and patients, because the word "can" contained in paragraph (1) of the regulation on medical practice could mean that the complaint to the Indonesian Medical Disciplinary Board may or may not be made. Whereas in paragraph (3) it is stated that it is possible to resolve medical disputes through the courts, which can cause medical dispute resolution to be carried out through the courts directly.